2016
DOI: 10.1021/acs.molpharmaceut.6b00461
|View full text |Cite
|
Sign up to set email alerts
|

Combining Stimulus-Triggered Release and Active Targeting Strategies Improves Cytotoxicity of Cytochrome c Nanoparticles in Tumor Cells

Abstract: Proteins often possess highly specific biological activities that make them potential therapeutics, but their physical and chemical instabilities during formulation, storage, and delivery have limited their medical use. Therefore, engineering of nano-sized vehicles to stabilize protein therapeutics and to allow for targeted treatment of complex diseases, such as cancer, is of considerable interest. A micelle-like nanoparticle (NP) was designed for both, tumor targeting and stimulus-triggered release of the apo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
43
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 32 publications
(48 citation statements)
references
References 35 publications
(81 reference statements)
5
43
0
Order By: Relevance
“…This system offers higher loading capacity in comparison to other nanocarriers because the core of the protein is made 100% of Cyt c, which is the drug itself. Our group has proved in previous studies the selectivity and effectivity of the decorated NPs in vitro, in HeLa cells, and in vivo, in glioma tumors [12,15]. In this study we demonstrate the superiority of the system when compared to an individual, FA-tagged Cyt c system.…”
Section: Introductionsupporting
confidence: 63%
See 2 more Smart Citations
“…This system offers higher loading capacity in comparison to other nanocarriers because the core of the protein is made 100% of Cyt c, which is the drug itself. Our group has proved in previous studies the selectivity and effectivity of the decorated NPs in vitro, in HeLa cells, and in vivo, in glioma tumors [12,15]. In this study we demonstrate the superiority of the system when compared to an individual, FA-tagged Cyt c system.…”
Section: Introductionsupporting
confidence: 63%
“…Several studies have shown that the direct external delivery of Cyt c to the cell cytosol can activate the caspase cascade and induce apoptosis in a dose-dependent manner [9,10]. Our group and others have developed several drug delivery systems for Cyt c which can induce apoptosis selectively in different cancer types by targeting the mitochondrial apoptotic pathway [11][12][13][14][15][16][17]. These systems specifically release the drugs under reducing conditions like the ones found in the cellular cytosol, but not outside the cell, increasing their effective dose and lowering off-targets and premature drug release [18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…CytoC binds apoptotic protease activating factor‐1 in the cytoplasm to activate caspase‐mediated apoptosis pathway . Efficient transport of CytoC to the cytoplasm of cancer cells results in significantly higher level of apoptosis . In addition, p53 gene, a tumor‐suppressor gene, is involved in inhibiting development and growth of tumors, and can induce apoptosis independently of the CytoC release .…”
Section: Introductionmentioning
confidence: 99%
“…It has the high affinity with folate receptors (FRs), which are over‐expressed in most tumor cells and low‐expressed in non‐epithelial tumors and normal tissue cells. Furthermore, it has the advantages of small size, stability, easy modification, and low production cost . FA ligands have been conjugated to Pluronic/polylactide and Pluronic/poly(lactide‐ co ‐glycolide) block copolymers previously by our groups.…”
Section: Introductionmentioning
confidence: 99%